MODERN SOCIAL CONTRADICTIONS OF MASS SPORT - Lubysheva, L.I.; Pashchenko, L.G. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to identify modern social contradictions of mass sports based on the analysis of youth involvement in physical culture and sports activities during leisure. Methods and structure of the study. In a specific sociological study, 930 young people aged 18 to 39 took part. The survey showed that 64.9% of respondents use the means of physical culture and sports during their leisure time. Most believe that these activities can contribute to career success. Of those involved in physical culture and sports activities, 34.4% prefer individual lessons, 37.1% - group lessons, the motives for doing them do not differ significantly. In both groups there are young people who avoid participation in competitions. 38.9% of the total number of those involved in physical culture and sports activities independently use the means of physical culture and sports at their leisure. Results and conclusions. The survey showed the inconsistency of the directions of mass sports - the "Sport for All" movement, focused on uniting those involved through the system of mass physical culture and sports events, is opposed to persons who are isolated in the process of independent physical culture and sports activities and avoid interaction with other participants.